2021
DOI: 10.3847/1538-4357/ac2d98
|View full text |Cite
|
Sign up to set email alerts
|

The X-Ray Outburst of PG 1553+113: A Precession Effect of Two Jets in the Supermassive Black Hole Binary System

Abstract: Blazar PG 1553+113 is thought to be a host of supermassive black hole binary system. A 2.2 yr quasi-periodicity in the γ-ray light curve was detected, possibly a result of jet precession. Motivated by the previous studies based on the γ-ray data, we analyzed the X-ray light curve and spectra observed during 2012–2020. The 2.2 yr quasi-periodicity might be consistent with the main-flare recurrence in the X-ray light curve. When a weak rebrightening in the γ-ray was observed, a corresponding relatively strong br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
4
12
1
Order By: Relevance
“…Yan et al (2018) claimed that the relativistic boost might result in the QPO of PG 1553+113 by cyclically varying Doppler factors. This finding is not at odds with previous studies (e.g., Caproni et al 2017;Cavaliere et al 2017;Sobacchi et al 2017;Tavani et al 2018;Huang et al 2021). However, the origin of the periodical Doppler factor is still under debate.…”
Section: Introductioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Yan et al (2018) claimed that the relativistic boost might result in the QPO of PG 1553+113 by cyclically varying Doppler factors. This finding is not at odds with previous studies (e.g., Caproni et al 2017;Cavaliere et al 2017;Sobacchi et al 2017;Tavani et al 2018;Huang et al 2021). However, the origin of the periodical Doppler factor is still under debate.…”
Section: Introductioncontrasting
confidence: 63%
“…Subsequently, Tavani et al (2018) took advantage of 9 yr data of Fermi-LAT and verified the 2.2 yr QPO of γ-ray exists in PG 1553+113. Huang et al (2021) confirmed that the 2.2 yr quasiperiodicity might be consistent with the recurrence of the primary flare on the X-ray light curve.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…(iii) Each black hole hosts a relativistic jet that contributes to the overall emission (Villata et al 1998;Huang et al 2021). The (quasi-)periodic variability is then introduced by the orientations of both jets.…”
Section: Discussionmentioning
confidence: 99%